Development and Application of an Activity Based Space-Time Accessibility Measure for Individual Activity Schedules - Olu Ashiru; John Polak; Robert B. Noland (European Regional Science Association (ERSA), 2003)
Accessibility is an important aspect of human existence impacting on our notion of society equity and justice. It plays an important role in a number of existing theories of spatial and travel behaviour in addition to affecting the rate and the pattern of land-use development. However despite the importance of the notion of accessibility, the accessibility measures, which have traditionally been used to quantify accessibility, have tended to be relatively poorly defined, excluding a wide range of observed forms of travel behaviour. This has ramifications for the implicit assumption underpinning the use of accessibility measures, namely that of a direct correlation between the measure of accessibility and individual travel behaviour. In this paper a hitherto unknown family of space-time route benefit measures are developed and utilised to derive an associated family of disaggregate activity based space-time utility accessibility measures. Applicable to individual activity schedules, these space-time activity accessibility measures implicitly acknowledge that travel is a derived demand. The paper commences with an outline of the limitations and primary assumptions present within traditional accessibility measures. The paper proceeds to provide a brief review of space-time user benefit measures highlighting their principle assumptions. Existing space-time locational benefit measures are subsequently extended to incorporate more realistic temporal constraints on activity participation and the perceived user benefit. The improved locational benefit measures incorporate a variety of factors including the utility an individual derives from activity participation, individual income, space-time constraints. In addition travel time, route delay and schedule disutility components such as the facility and activity wait times associated with early arrival are incorporated, in addition to late start time penalties associated with late commencement of an activity. The improved space-time locational benefit measure is subsequently applied to activity schedules incorporating a series of multiple linked activities. The paper subsequently demonstrates how the resulting user benefit measure can be shown to be part of a broader family of space-time route benefit measures, which despite their theoretical attractiveness have hitherto not been utilised by researchers. An associated family of space-time utility accessibility measures are subsequently developed and the paper proceeds to highlight how stochastic frontier models utilised in conjunction with existing travel/activity diary datasets can be utilised to operationalise the proposed measure of accessibility. The proposed family of accessibility measures are implemented within a point based spatial framework encompassing detailed spatially referenced land-use transportation network encompassing public transport, cycle, walk and car transport modes. Several practical examples are presented of the proposed family of accessibility measures in use and in particular demonstrate the strength and potential of the methodology in developing a wide range of transport-land-use policies. Examples are presented of the use of the methodology in developing new/improved transport links and services, the provision of additional land-use facilities/opportunities, extended opening of facilities/opportunities, the identification of transport related social exclusion, the development of equitable land-use transport schemes and policies as well as the development of flexible working policies. The paper concludes with a summary highlighting the principle benefits and properties of the proposed family of accessibility measures in addition to highlighting potential areas of future research.
Keywords: 330